The use of Sunda Manda games to stimulate early childhood numerational intelligence - Yuniati, Rina; Kristiana, Dian; Rusdiani, Nurtina Irsad (Pusat Studi Gender dan Anak, 2024)
The importance of early childhood multiple intelligences lied in the fact that every child possesses unique talents and potential. Various forms of intelligence, including verbal, mathematical reasoning, visual-spatial, musical, interpersonal, intrapersonal, kinesthetic, and naturalistic, enable educators to adapt learning approaches to meet the unique needs of each child. This study aims to enhance the numerical aptitude of children between the ages of 4 and 5 by utilizing the Sunda Manda number game at the Dharma Wanita Nadi II Kindergarten, Bulukerto. This study employs descriptive qualitative methodologies. The data collection process involved triangulation, including interviews with teachers from class A to gather information. Additionally, observations were made while the children were playing Sunda Manda numbers. Documentation was also done while playing Sunda Manda numbers to record relevant information about the children. The participants in the study consisted of teachers and pupils classified as class A, with an age range of 4-5 years. The research findings indicate that the Sunda Manda game numbers can enhance numeracy intelligence in children with auditory processing disorders associated with symbolic thinking, logical thinking, and learning and problem-solving abilities. Then, the game also promotes children's physical development through three stages: education, expansion, and development.